Incremental detection rate of prostate cancer by real‐time elastography targeted biopsies in combination with a conventional 10‐core biopsy in 1024 consecutive patients. (14th February 2014) - Salomon, Georg; Drews, Nils; Autier, Philippe; Beckmann, Ann; Heinzer, Hans; Hansen, Jens; Michl, Uwe; Schlomm, Thorsten; Haese, Alex; Steuber, Thomas; Graefen, Markus; Becker, Andreas
Abstract : Objective: To quantify the incremental detection rate (DR) of a targeted biopsy in addition to a randomized 10‐core biopsy. Patients and Methods: This retrospective study analysed 1024 patients who consecutively underwent a four‐core real‐time elastography (RTE) targeted biopsies in addition to a randomized 10‐core transrectal ultrasonography (TRUS)‐guided biopsy in a primary or rebiopsy setting. The overall DR, the DR of a 10‐core randomized, RTE targeted biopsy and the incremental DR were calculated. Results: Overall, randomized and RTE targeted biopsy DRs (for the combination, the 10‐core and the four‐core RTE biopsy scheme) were 46.2% ( n = 473), 39.1% ( n = 400) and 29.0% ( n = 297), respectively. Four‐core RTE targeted biopsies detected an additional 73 patients not detected by the 10‐core randomized biopsies (increase in the overall DR of 7.1%). This represented a relative increase in DR of 18.3%. The incremental DR was better in rebiopsy patients (24.8%) than in patients having their first biopsy (14.7%). Within all patients diagnosed by RTE targeted biopsy only, 34 patients harboured significant Gleason 4 or 5 prostate cancer (PCa), diagnosed by four‐core RTE biopsy only. Moreover, PCa with a Gleason grade of 4 or 5 was detected by four‐core RTE biopsies in 30 patients, who showed low‐grade PCa ≤ Gleason 3 only in the systematic 10‐core biopsy. Conclusions: Real‐time elastography targeted biopsy seems to be an appropriate method for increasing the DR of PCa. Nevertheless, RTE targeted biopsies missed a high proportion of patients with PCa and should therefore be considered as an addition to randomized biopsies.